Listening to music during a repeated sprint test improves performance and psychophysiological responses in healthy and physically active male adults - Nidhal Jebabli; Abderraouf Ben Aabderrahman; Daniel Boullosa; Hamdi Chtourou; Nejmeddine Ouerghi; Fatma Rhibi; Karuppasamy Govindasamy; Ayoub Saeidi; Cain C. T. Clark; Urs Granacher; Hassane Zouhal (BMC, 2023)
Abstract Background It is well-documented that listening to music has the potential to improve physical performance during intense physical exercise. Less information is available on the timing of music application. This study aimed to investigate the effects of listening to preferred music during the warm up of a subsequent test or during the test on performance of repeated sprint sets (RSS) in adult males. Methods In a randomized cross-over design, 19 healthy males (age, 22.1 ± 1.2 years; body mass, 72.7 ± 9.3 kg; height, 1.79 ± 0.06 m; BMI, 22.6 ± 2.2 kg m−2) performed a test including 2 sets of 5*20-m repeated-sprints under one of three conditions: listening to preferred music during the test; listening to preferred music during the warm-up; or not listening to music. The assessed parameters comprised RSS performance indices, blood lactate, heart rate, the pacing strategy profile, rating of perceived exertion, and a feeling scale. Results For performance indices during set 1 of the RSS test, we found a significant decrease in total sum sequence, fast time index and fatigue index in the listening to preferred music condition compared to the no music condition (total sum sequence: p = 0.006, d = 0.93; fast time index: p = 0.003, d = 0.67; fatigue index: p < 0.001; d = 1.30) and the listening to preferred music during the warm-up condition (fast time index: p = 0.002; d = 1.15; fatigue index: p = 0.006; d = 0.74). However, there was no significant effect of listening to preferred music on physical performance during set 2 of the RSS test. Compared to the no music condition, blood lactate concentrations were higher in the listening to preferred music during the test condition (p = 0.025; d = 0.92). In addition, listening to preferred music appears not to have an effect on heart rate, the pacing strategy profile, perceived exertion, and affective responses before, during and after the RSS test. Conclusion Findings from this study revealed that RSS performances were better (FT and FI indices) in the PMDT compared with the PMWU condition. Moreover, in set 1 of the RSS test, better RSS indices were found in the PMDT compared to NM condition.